Physical strain of handcycling: An evaluation using training guidelines for a healthy lifestyle as defined by the American College of Sports Medicine. (1st July 2013) - Hettinga, Florentina J.; de Groot, Sonja; van Dijk, Frank; Kerkhof, Faes; Woldring, Ferry; van der Woude, Luc
Abstract : Objective Developments in assistive technology such as handcycling provide attractive possibilities to pursue a healthy lifestyle for patients with spinal cord injury. The objective of the study is to evaluate physical stress and strain of handcycling against training guidelines as defined by the American College of Sports Medicine (ACSM). Design Seven able-bodied males conducted an incremental peak exercise handcycling test on a treadmill. In addition, two indoor treadmill (1.3 m/second with an inclination of 0.7% and 1.0 m/second with an inclination of 4.8%) and three outdoor over ground exercise bouts were performed (1.7, 3.3, and 5.0 m/second). One individual handcycled a representative 8-km-distance outdoors. Outcome measures Physical stress and strain were described in terms of absolute and relative power output, oxygen uptake (VO2 ), gross efficiency (GE), and heart rate (HR). Also, local perceived discomfort (LPD) was determined. Results Relative handcycling exercise intensities varied between 23.3 ± 4.2 (below the ACSM lower limit of 46%VO2peak ) and 72.5 ± 15.1%VO2 peak (well above the ACSM lower limit), with GE ranging from 6.0 ± 1.5% at the lower to 13.0 ± 2.6% at the higher exercise intensities. Exercise intensities were performed at 49.8 ± 4.2 to 80.1 ± 10.5%HRpeak . LPD scores were low to moderate (<27 ± 7). Conclusion Handcycling is relatively efficient and exercise intensities > 46%VO2peak were elicited. However, exercise load seems to be underestimated using %HRpeak . LPD was not perceived as limiting. Physiological stress and strain in able-bodied individuals appear to be comparable to individuals with a paraplegia. To understand individualize and optimize upper-body training, different training programs must be evaluated.